Simple Bond-Graph Model To Predict Dried Material Temperature Evolution in A Batch Type Rotary Dryer - Waluyo, Sugeng; Ardiansyah, Ardiansyah; Latifasari, Nurul; Kartiko, Condro; Arsil, Poppy; Wicaksono, Rumpoko; Aliim, Muhammad Syaiful; Naufalin, Rifda (JMES The International Journal of Mechanical Engineering and Sciences, 2024)
In this work, we model temperature evolution inside a batch type rotary dryer by using the bond-graph method. The evolution model proposed here is mainly developed to predict dried material temperature inside the dryer during drying process. We implement the model in the 20-SIM bond-graph simulator (Controllab Products, the Netherlands) which shows realistic behaviors of the dried material temperature evolution with different combustion scenarios and rotation speeds.